Cell-phone origin identification based on spectral features of device self-noise - Anshan PEI; Rangding WANG; Diqun YAN (Dianxin kexue)
With the widespread availability of cell-phone recording devices and the availability of various powerful and easy-to-use digital media editing software,source cell-phone identification has become a hot topic in multimedia forensics.A novel cell-phone identification method was proposed based on the recorded speech.Firstly,device self-noise (DSN) was considered as the fingerprint of the cell-phone and estimated from the silent segments of the speech.Then,the mean of the noise's spectrum was extracted as the identification.Principal components analysis (PCA) was applied to reduce the feature dimension.Support vector machine (SVM) was adopted as the classifier to determine the source of the detecting speech.Twenty-four popular models of the cell-phones were evaluated in the experiment.The experimental results show that the average identification accuracy and recall of the method can reach up to 99.24% and demonstrate that the self-noise feature has more superior performance than the MFCC feature.